1990
DOI: 10.1161/01.hyp.16.6.682
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil amplifies the effect of propranolol in mild essential hypertension.

Abstract: Forty-seven male patients with mild essential hypertension were randomly allocated to three subgroups. After a run-in period of 4 weeks, the first subgroup (n=16) received propranolol (80 mg/day) for 36 weeks followed by a placebo period of 4 weeks. The second subgroup (n=15), after a run-in period of 4 weeks, was given a supplement of encapsulated fish oil (9 g/day) for 36 weeks with a subsequent period of 4 weeks in which fish oil placebo was given. The third subgroup (n=16), after a run-in period of 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…They found that, after fish oil supplementation, plasma NE levels were reduced to 80% of the baseline value in Group F and 56% of that in Group P+F. The reduction levels of plasma NE were similar to our study (18). However, their findings were excep tional because no other controlled studies have found any significant decreases in plasma NE during fish oil treatment with normal subjects (19,20) or mild hy pertensives (19,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…They found that, after fish oil supplementation, plasma NE levels were reduced to 80% of the baseline value in Group F and 56% of that in Group P+F. The reduction levels of plasma NE were similar to our study (18). However, their findings were excep tional because no other controlled studies have found any significant decreases in plasma NE during fish oil treatment with normal subjects (19,20) or mild hy pertensives (19,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 88%
“…However, their findings were excep tional because no other controlled studies have found any significant decreases in plasma NE during fish oil treatment with normal subjects (19,20) or mild hy pertensives (19,(21)(22)(23). Although experimental protocols differed from study to study and no direct comparison of these studies seemed possible, the plasma NE levels before fish oil administration were rather high in the study of Singer et al (18) that found the NE-reducing activity of fish oil. Our subjects had also rather high baseline plasma NE levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This increase, together with a relative reduction in high density lipoprotein (HDL) cholesterol, has favoured the use of newer, 'lipid-neutral' antihypertensive drugs. With these metabolic effects in mind and considering evidence from Singer et al (1990) that fish oil can enhance the antihypertensive effect of the P-blocker propanolol, we set up another study in collaboration with general practitioners to test the effects of a fish oil supplement on both lipids and BP in hypertensives taking a P-blocker and/or diuretic (Lungershausen et al 1994).…”
Section: Fish Oil As An Adjunct Antihypertensive Therapymentioning
confidence: 99%
“…Fish oil ampli ed the hypotensive action of the b-adrenergic receptor blocker propranolol, in mild-to-moderate hypertensives [48]. A study by Bao et al [9] demonstrated that blood pressure reduction was further enhanced in obese treated hypertensives, when sh oils were combined with a weight loss program.…”
Section: Fish and Fish Oilsmentioning
confidence: 99%